THE EFFECTIVENESS OF CHAIN-STORY STRATEGY IN WRITING ACHIEVEMENT OF THE TENTH GRADE STUDENTS OF MA DARUL ULUM NGABAR MOJOKERTO - Sonya Brinda (Jurnal Bahastra, 2019)
Writing has become one of the important skills for students in learning English. In addition, writing skills can help them improve their educational knowledge. Writing also became an important tool for learning the discipline and practiced students' vocabulary. Teachers had several ways to improve students' writing skills, one of them was by applying the chain story strategy. This research was aimed to determine the effectiveness of chain-story strategy for the tenth grade students’ writing skill achievement at MA Darul Ulum Ngabar Mojokerto in 2018/2019 academic years. The research design was pre-experimental design with the tenth-grade students as the population. From those population, it was determined if X IPS-1 class become the data through random sampling technique. Data were analyzed using the T-test formula. At the same time as the data was collected, the researchers conducted a pre-test and a post-test through a written test. The df was 29 and the results at a significant level of 5% was 1,699. It could be seen from the results of ΣX: 1801, ΣY: 2480, ΣD: 683.75, ∑ : 18095.41. This showed that chain-story strategy is applied to the value of students’ writing skill. The results showed that the result of the T-test was 13.48. The alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. Therefore, the alternative hypothesis (Ha) has shown that the chain story strategy in writing achievements is effectively accepted.